2022
DOI: 10.3389/fnmol.2022.925272
|View full text |Cite
|
Sign up to set email alerts
|

Harmane Potentiates Nicotine Reinforcement Through MAO-A Inhibition at the Dose Related to Cigarette Smoking

Abstract: Nicotine is the primary addictive component in cigarette smoke, and dopamine release induced by nicotine is considered a significant cause of persistent smoking and nicotine dependence. However, the effects of nicotine replacement therapy on smoking cessation were less effective than expected, suggesting that other non-nicotine constituents may potentiate the reinforcing effects of nicotine. Harmane is a potent, selective monoamine oxidase A (MAO-A) inhibitor found in cigarette smoke, but showed no effect on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…A similar trend was found in DA release (Figures 3D-F). When administrated with nicotine, the peak value of abnormal release of DA in the NAc was about 135% above the base level, which was similar to other studies using microdialysis (Rada et al, 2001;Ding et al, 2022); this observation supported the reliability of using the DA biosensor to monitor drug-induced DA release, while DNC further enhanced the DA peak value of nicotine to 157% (Figure 3D).…”
Section: Discussionsupporting
confidence: 87%
“…A similar trend was found in DA release (Figures 3D-F). When administrated with nicotine, the peak value of abnormal release of DA in the NAc was about 135% above the base level, which was similar to other studies using microdialysis (Rada et al, 2001;Ding et al, 2022); this observation supported the reliability of using the DA biosensor to monitor drug-induced DA release, while DNC further enhanced the DA peak value of nicotine to 157% (Figure 3D).…”
Section: Discussionsupporting
confidence: 87%
“…In addition to DYRK1A, harmine also inhibits monoamine oxidase A ( 43 45 ). To determine if the compound affects HIV-1 through inhibition of MAO A, we tested two other MAO A inhibitors, harmane ( 22 ) and moclobemide ( 23 ), for their ability to affect HIV-1 gene expression in two different cell lines: HeLa B2 and CEM-HIV cells. In contrast to harmine, neither harmane nor moclobemide significantly reduced HIV-1 gene expression in either of these cell systems ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HeLa B2 and CEM-HIV cells were used to examine the effect of other monoamine oxidase A inhibitors, harmane ( 22 ) (10 µM) and moclobemide ( 23 ) (30 µM), for their anti-HIV-1 activity together with harmine. Cells were plated on 12-well dish and induced and treated with compounds, after which the lysates were harvested to monitor HIV-1 protein levels by western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…Smokers with more active enzymes are required to consume higher amounts of tobacco to achieve an inhibiting effect on MAO-A compared to smokers with genetically encoded lower enzyme activity. In our previous research, we found that harmane, a potent and selective MAO-A inhibitor present in cigarette smoke, may also play a significant role in nicotine dependence [ 126 ]. The inhibition of MAO-A activity increases the actions of dopamine and other monoamine neurotransmitters that are responsible for drug reinforcement and motivation [ 127 ], thus exacerbating susceptibility to nicotine dependence.…”
Section: Polymorphisms In Genes Associated With Dopamine Degradationmentioning
confidence: 99%